Managing Family Finances During The COVID-19 Pandemic - Yusuf Rombe M. Allo; Lis Sintha; Edison Siregar; Riwandari Juniasti (Golden Ratio of Community Services and Dedication, 2021)
This community service activity (PPM) aims to increase the understanding of the Methodist Indonesia Sungai Yordan Church congregation in managing business finances/side businesses to develop well and manage family finances to achieve specific funding targets in the future. To protect and increase the wealth owned; to manage cash flow (incoming and spending money); to carry out risk management and manage risks appropriately, and to manage accounts payable correctly and adequately. The method used is by conducting counseling and distributing online questionnaires to determine financial conditions during the pandemic. Based on the questionnaire results, most of the church members who attended stated that they could overcome financial difficulties during the pandemic with the income they received every month. The chosen investment method is savings and gold to be quickly withdrawn/sold during a pandemic.